Aspectos morfométricos de cuencas subtropicales del Noroeste de Argentina - Díaz Gómez, Andrea Romina (2017)
The hydrological basin located on the eastern slopes of the mountains in the Northwest Argentina are characterized by a marked break in the slope piedmont Transition, orographic rainfall, flood events and few hydrometric records. Morphometric parameters used to define the interaction between geological and geomorphological characteristics, and surface physical patterns, characterizing quantitatively the possible response of the basin to a hydrologicalscenario. The objective of this study was to quantify the morphometric characteristics of the hydrological basins of the eastern slope of the Aconquija Ranges (FOA, acronym for Faldeo Oriental del Aconquija) and Southwest Ranges of Tucumán (SS). Through a comparative analysis,using geographic information systems and hydrological model HEC-Geo HMS ® base on the Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER GDEM) digital elevation model. The results suggest that the FOA and SS watersheds are the most elongated and classified as medium-sized basins. Comparatively the Balderrama and Romano Basins have major erosion potential than the Gastona and Río Chico Basins. In the same way, in the SS Basins, Chavarría and Singuil Basins have major torrential characteristics (concentration times less than 7 hours) than Marapa and Matazambi Basins (concentration greater than 10 hours). The maps and the new data (tables) obtained have a direct application in the proposals of watershed management plans.